Interventions and quality of life in stress urinary incontinence - Deeksha Pandey; Chaitanya Maturi; Bhanu Pratap Singh Dhakar; Gazal Jain; Keerti Kyalakond (Wolters Kluwer Medknow Publications, 2019)
Introduction: Stress urinary incontinence (SUI), though is more prevalent than many chronic diseases, has remained largely underreported and underdiagnosed condition. We aimed to find the improvement in the quality of life (QoL) of women with SUI after individual interventions, namely mid-urethral sling (MUS), pelvic floor muscle training (PFMT), and no treatment/control group, as primary treatment modalities. Materials and Methods: This was a prospective interventional case-control study conducted at a university teaching hospital, over a period of 2 years. Parous women with at least one vaginal delivery, attending the gynecology outpatient department, were encouraged to fill the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form. Those with SUI were divided into three arms (MUS, PFMT, and no treatment/control group), according to the informed decision for choice of management. Baseline QoL was documented for all with King's Health Questionnaire. QoL was again recorded after 3 months of the start of treatment and was compared with the baseline. Results: In our study cohort, the prevalence of SUI was 15.2%, with a consultation rate of only 30.7%. MUS surgery improves QoL significantly in women with SUI, followed by PFMT. We found 100% symptomatic relief, high rate of improvement in QoL with minimal easy to manage complications, in the surgical intervention arm. PFMT, though has a positive impact on QoL, requires continuous motivation, as 22% discontinued. Without treatment, QoL in SUI patients remained more or less the same. Conclusion: The help-seeking behavior (consultation rate) for SUI is poor. MUS (surgical arm) had 100% symptom relief in 3-month follow-up. MUS showed the best results in terms of QoL improvement, followed by PFMT in SUI in our study. It is important not only to educate women about the problem but also to encourage them to seek treatment and indicate that it is a treatable condition.